ANALISIS DAYA SAING DAN MODEL PEMASARAN SAYUR HIDROPONIK DI KABUPATEN SAMBAS - Dian Sari, Wilis Widi Wilujeng, Uray Dian Novita (PPPM POLTESA, 2022)
The purpose of this study was to analyze the competitiveness and market size and to formulate a marketing strategy for hydroponic vegetable business in Sambas Regency. Research conducted in Sambas Regency. The data used in this study are primary and secondary data. Data processing and analysis techniques used descriptive qualitative methods, Porter's Diamond Theory and SWOT. The results of the competitiveness analysis using Porter's Diamond Theory, it can be seen that the level of competitiveness of hydroponic vegetables is that they are sufficiently competitive among fellow vegetable business actors. and also resource factors with related and supporting industry components. The results of the SWOT analysis Marketing model development The suitable strategy to be applied is an intensive strategy namely market penetration, market development and product development. Keywords: Competitiveness, Hydroponic Vegetables, Marketing Strategy